2007
DOI: 10.1111/j.1467-9507.2007.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Solitude: Young Children's Attitudes and Responses Toward Hypothetical Socially Withdrawn Peers

Abstract: The goal of the present study was to explore young children's attitudes and responses to different forms of social withdrawal by eliciting responses to hypothetical vignettes. Participants included 137 children (49 boys, 88 girls) in kindergarten and grade 1 classes (M age = 75.94 months, SD = 9.03) in Ottawa, Canada. Parents rated child characteristics, including shyness, unsociability and aggression. Children were also interviewed individually and presented with a series of hypothetical vignettes describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
3
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 84 publications
(147 reference statements)
6
109
3
10
Order By: Relevance
“…Past studies, however, have found fathers to be particularly discouraging of sons' shyness (Coplan et al 2007;Mills and Rubin 1993), which runs counter to the present study's finding that shy, poorly accepted daughters had particularly non-responsive fathers. Consonant with the current findings, however, other studies suggest that father involvement may be as salient an influence on daughters as it is on sons (Crouter et al 1993;Dubowitz et al 2001;Flouri and Buchanan 2003).…”
Section: Discussioncontrasting
confidence: 86%
“…Past studies, however, have found fathers to be particularly discouraging of sons' shyness (Coplan et al 2007;Mills and Rubin 1993), which runs counter to the present study's finding that shy, poorly accepted daughters had particularly non-responsive fathers. Consonant with the current findings, however, other studies suggest that father involvement may be as salient an influence on daughters as it is on sons (Crouter et al 1993;Dubowitz et al 2001;Flouri and Buchanan 2003).…”
Section: Discussioncontrasting
confidence: 86%
“…Thus, it should not be surprising that social withdrawal is also associated with loneliness and depressed affect from the earliest years of childhood through early adolescence (e.g., Coplan et al 2007, Eisenberg et al 1998, Hymel et al 1990, Prior et al 2000. Moreover, the combination of withdrawal and peer rejection, exclusion, and/or victimization appears to be the strongest predictor of these negative outcomes (e.g., Bell-Dolan et al 1995, Boivin & Hymel 1997, Gazelle & Ladd 2003, Gazelle & Rudolph 2004, supporting the premise that it is the negative response of the peer group that results in withdrawn children's internalized negative thoughts and feelings.…”
Section: Self and Social Cognitionsmentioning
confidence: 99%
“…Results from recent research indicate that parents ), teachers (Arbeau & Coplan 2007, Thijs et al 2004, and even young children (Coplan et al 2007) distinguish between social disinterest and other forms of social withdrawal (e.g., shyness). In early childhood, there is evidence to suggest that social disinterest is comparably benign (e.g., Asendorpf & Meier 1993, Harrist et al 1997.…”
Section: Future Directions Other Forms Of Social Withdrawalmentioning
confidence: 99%
“…Shy / withdrawn temperament is characterized by extraordinary fear, contingency and timid behavior in foreign situations (Kagan et al, [24]) and shyness is one form of social withdrawal (Rubin and Asendorpf, [38] ). In another definition shyness is defined as "caution, anxiety and perceived social assessment in the face of social innovation" (Coplan et al, [6] ). From a slightly different perspective, "shyness" has been conceptualized as a (congenital) shy behavior in the context of social innovation or social assessments.…”
Section: Introductionmentioning
confidence: 99%